DARI MEJA MAKAN KE MEJA PERSEKUTUAN: REKONSTRUKSI RELASI KELUARGA KRISTEN YANG HARMONIS DALAM MENGHADAPI PERKEMBANGAN ZAMAN - Martin Hasonangan Silaen; Riris Johanna Siagian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This paper discusses the shifting meaning of the family dining table in Christian households within the context of modern social and cultural changes marked by individualism, busyness, and weakened communication among family members. The dining table, once a symbol of togetherness, love, and intimate relationships within the family, has increasingly lost its function as a space for dialogue and fellowship. This shift affects the quality of Christian family relationships, which should be the primary place for nurturing faith, love, and Christian character. Through theological reflection, this paper seeks to reconstruct the meaning of the “dining table” into the “table of fellowship” as a symbol of God’s presence in family life. The table of fellowship is not merely a place for sharing food but also a sacred space where the family experiences grace, forgiveness, and renewed relationships, as reflected in the Holy Communion. From the perspective of contextual theology, Christian families are called to reorganize their lives so that the values of togetherness, communication, and love may be revitalized amid the challenges of the digital era and the instant culture that erodes relational intimacy. This study emphasizes that the renewal of Christian family relationships begins with a theological awareness that every meal shared at the table can become a spiritual fellowship that manifests Christ’s love. The research employs a descriptive qualitative method through theological literature review and contextual reflection to analyze the symbolic meaning of the table in forming a harmonious Christian family.